Obstructive Jaundice due to Pancreatic Involvement as an Initial Presentation of Adult Acute Lymphoblastic Leukemia - Oreoluwa Oladiran; Ifeanyi Nwosu (Case Reports in Hematology)
Acute lymphoblastic leukemia (ALL) is a heterogeneous group of lymphoid disorders characterized by monoclonal proliferation and expansion of immature lymphoid cells in the bone marrow, blood, and other organs. It commonly presents with nonspecific symptoms such as lethargy, easy bruising, and weight loss. In this article, we present the case of a 48-year-old male who presented to the hospital with painless jaundice resulting from pancreatic infiltration, initially thought to be due to pancreatic or hepatobiliary malignancy. He was later diagnosed with ALL by lymph node biopsy and peripheral blood flow cytometry immunophenotyping and was transferred to a cancer treatment centre for unilateral bone marrow biopsy and further management. Our case highlights the rare occurrence of pancreatic infiltration in ALL.